Revitalise your knowledge thru clinical data interpretation - Zarida Hambali; Intan Nureslyna Samsudin; Thambiah, Subashini C. (Universiti Putra Malaysia Press, 2013)
This book is an ideal overview and revision guide for medical students, postgraduate students, house-officers, general practitioners, nurses and health scientists. This book is written to highlight the importance of correlating clinical presentations